Hubungan Upaya Pencegahan dan Penerapan Keselamatan Kesehatan Kerja dengan Kecelakaan Kerja Pada Pekerja Indonesia di Departemen Operasional Perusahaan Gas Qatar - Vidi Viciyandrie; Erislan Erislan; Soehatman Ramli (Universitas Malahayati Lampung, 2023)
ABSTRACT Companies in the gas sector are growing rapidly to become one of the largest income centers in the Qatar region, and have strict work routines which are still found to have 1-2% of work accidents, human performance errors, which are closely related to minimizing them by increasing efforts to prevent and implement occupational health and safety. The aim of the research is to analyze the relationship between efforts to prevent and implement occupational health safety and work accidents among Indonesian workers in the Qatar Gas Company Operations Department. The research method is a descriptive type of correlation, cross sectional approach. The total sample was 125 Indonesian workers with a sampling technique using random sampling. The instruments used were questionnaires that were valid and reliable, including prevention effort questionnaires (Cronbach Alpha value 0.987), occupational safety and health application questionnaires (Cronbach Alpha value 0.953) and work accident questionnaires (Cronbach Alpha value 0.932). Univariate data analysis uses frequency distribution calculations and bivariate data analysis uses the Chi-Square test. The research results show that the majority (74.4%) of Indonesian workers' prevention efforts are high, the majority (62.4%) of Indonesian workers' occupational safety and health practices are good and the majority (56.8%) of Indonesian workers do not experience work accidents. There is a relationship between prevention efforts (p-value 0.001) and implementation of occupational health safety (p-value 0.000) with work accidents among Indonesian workers in the Qatar Gas Company Operations Department.: Recommendations for Indonesian workers need to improve their personal competence through training or regularly attending workshops on the implementation of occupational health safety and work accident prevention efforts to minimize work accidents. Keywords : Occupational Accidents, Implementation of Occupational Health Safety, Prevention Efforts ABSTRAK Perusahaan dibidang gas berkembang pesat menjadi salah satu pusat penghasilan terbesar wilayah Qatar, memiliki rutinitas kerja yang ketat yang masih ditemukan kejadian kecelakaan kerja 1-2% human error kinerja yang berkaitan erat untuk meminimalisirnya dengan peningkatan upaya pencegahan dan penerapan keselamatan kesehatan kerja. Tujuan penelitian untuk menganalisis hubungan antara upaya pencegahan dan penerapan keselamatan kesehatan kerja dengan kecelakaan kerja pada pekerja Indonesia di Departemen Operasional Perusahaan Gas Qatar. Metode penelitian jenis desktriptif korelasi pendekatan cross sectional. Jumlah sampel sebanyak 125 pekerja Indonesia dengan teknik pengambilan sampel menggunakan random sampling. Instrumen yang digunakan adalah kuesioner yang telah valid dan reliabel meliputi kuesioner upaya pencegahan (nilai Cronbach Alpha 0,987), kuesioner penerapan keselamatan kesehatan kerja (nilai Cronbach Alpha 0,953) dan kuesioner kecelakaan kerja (nilai Cronbach Alpha 0,932). Analisis data univariat menggunakan perhitungan distribusi frekuensi dan analisis data bivariat menggunakan uji Chi- Square.Hasil penelitian menujukkan sebagian besar (74,4%) upaya pencegahan pekerja Indonesia tinggi, sebagian besar (62,4%) penerapan keselamatan kesehatan kerja pekerja Indonesia baik dan sebagian besar (56,8%) pekerja Indonesia tinggi tidak mengalami kejadian kecelakaan kerja. Terdapat hubungan antara upaya pencegahan (p-value 0,001) dan penerapan keselamatan kesehatan kerja (p-value 0,000) dengan kecelakaan kerja pada pekerja Indonesia di Departemen Operasional Perusahaan Gas Qatar. Rekomendasi bagi pekerja Indonesia perlu meningkatkan kompetensi diri melalui pelatihan atau rutin mengkuti workshop tentang penerapan keselamatan kesehatan kerja dan upaya pencegahan kecelakaan kerja untuk memimalisir kecelakaan kerja. Kata Kunci: Kecelakaan Kerja, Penerapan Keselamatan Kesehatan Kerja, Upaya Pencegahan